Prevalence and Factors Associated With Liver Fibrosis Among Adult HIV-Infected Patients Attending Urban and Rural Care Clinics in Uganda. (13th October 2020) - Wekesa, Clara; Kirk, Gregory D; Aizire, Jim; Benson, Eve-Marie; Karabarinde, Alex; Parkes-Ratanshi, Rosalind; Ocama, Ponsiano
Abstract: Background: Liver fibrosis is common among HIV-infected patients. Risk factors vary by location. Understanding this variation may inform prevention strategies. We compared the prevalence and correlates of liver fibrosis among HIV-infected patients attending care clinics in Uganda. Methods: This was a cross-sectional study involving 2030 HIV-infected patients attending care clinics in urban and rural Uganda. Liver fibrosis was defined as liver stiffness measurement (LSM) >7.1 KPa. Proportions and correlates of liver fibrosis were assessed and compared using logistic regression stratified by gender and site. Results: Prevalence of liver fibrosis was higher among participants in the rural clinic (15% vs 11%; P = .017). History of tobacco use (urban P = .022; rural P = .035) and serologic evidence of hepatitis C infection (HCV; urban P = .028; rural P = .03) was associated with liver fibrosis in all men. Elevated liver transaminases (urban P = .002; rural P = .028) and increasing age (urban P = .008; rural P = .052) were risk factors among all women. Tobacco use among women was only a risk factor in those attending the rural clinic ( P = .003), and detectable HIV viral load ( P = .002) for men in the urban clinic. Conclusions: Liver fibrosis is prevalent among HIV-infected persons in Uganda. HIV viral suppression and avoiding tobacco may be strategies to prevent liver fibrosis and cancer risk.